Seriality’s Ludic Promise: Film Serials and the Pre-History of Digital Gaming - Higgins, Scott (Eludamos: Journal for Computer Game Culture, 2014)
This essay explores the American Sound Serial film as part of a continuum to which digital gaming may also belong. By drawing on concepts derived from the study of video games, this study broadens our understanding of youth-oriented films produced in Hollywood from the 1930s to the mid 1950s. In turn, this provides a new vantage on continuities between old and new serial forms, and sheds light on digital gaming’s pre-history.